2015
DOI: 10.1177/0310057x1504300303
|View full text |Cite
|
Sign up to set email alerts
|

Debriefing after Simulation-Based Non-Technical Skill Training in Healthcare: A Systematic Review of Effective Practice

Abstract: Non-technical skills training in healthcare frequently uses high-fidelity simulation followed by a facilitated discussion known as debriefing. This type of training is mandatory for anaesthesia training in Australia and New Zealand. Debriefing by a skilled facilitator is thought to be essential for new learning through feedback and reflective processes. Key elements of effective debriefing need to be clearly identified to ensure that the training is evidence-based. We undertook a systematic review of empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 56 publications
1
87
0
12
Order By: Relevance
“…In the field of simulation, the use of video-assisted debriefing is not superior to the use of non-video-assisted debriefing for the acquisition of technical and non-technical skills (18). However, regarding non-technical skills, as stated in two reviews, no study specifically analyzed the impact of the debriefing structure on learners’ perceptions and performance (19, 20). …”
Section: Discussionmentioning
confidence: 99%
“…In the field of simulation, the use of video-assisted debriefing is not superior to the use of non-video-assisted debriefing for the acquisition of technical and non-technical skills (18). However, regarding non-technical skills, as stated in two reviews, no study specifically analyzed the impact of the debriefing structure on learners’ perceptions and performance (19, 20). …”
Section: Discussionmentioning
confidence: 99%
“…Also, the long-term effects of debriefing are uncertain, according to Couper et al 13 Others have reported that the method of debriefing is more important than the timing for debriefing, 26 and debriefing by a skilled facilitator is more essential for new learning and reflective processes. 27 Cheng et al 1 recommended five issues to address for the future of debriefing training: (1) the appropriate debriefing methods, (2) the appropriate methods to teach debriefing skills, (3) the best methods to assess debriefing effectiveness, (4) to improve debriefing quality by peer feedback, and (5) to provide for the learning needs of educators by individualizing of debriefing training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The costs and scheduling challenges to recruiting trained instructors is a serious limitation to the implementation of simulation curricula (Rudolph, Simon, Dufresne, & Raemer, 2006). Researchers have considered alternative forms of debriefing that emphasise formative self-assessment, i.e., assessment for the purpose of learning (Eppich & Cheng, 2015;Garden, Le Fevre, Waddington, & Weller, 2015). For example, self-debriefing has been shown to be effective in improving CRM skills of individual anaesthesiology trainees during simulated crisis scenarios Garden et al, 2015;Tannenbaum & Cerasoli, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have considered alternative forms of debriefing that emphasise formative self-assessment, i.e., assessment for the purpose of learning (Eppich & Cheng, 2015;Garden, Le Fevre, Waddington, & Weller, 2015). For example, self-debriefing has been shown to be effective in improving CRM skills of individual anaesthesiology trainees during simulated crisis scenarios Garden et al, 2015;Tannenbaum & Cerasoli, 2013). Debriefing among teams without an instructor present has been found to be comparable to instructor-led debriefings to improve CRM in interprofessional teams .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation